FORMULATION AND CHARACTERIZATION OF STOMACH TARGETED MUCOADHESIVE TABLETS OF RANITIDINE HYDROCHLORIDE - MAHESWARAPPA CHATTER,; S. A. SREENIVAS, (International Journal of Pharma and Bio Sciences, 2016)
Ranitidine is a non-imidazole blocker of those histamine receptors that mediate gastric secretion (H2 receptors). It is used to treat gastrointestinal ulcers. The aim of the present work is to prolong the drug retention time of ranitidine hydrochloride by formulating the stomach targeted mucoadhesive tablets using various bioadhesive polymers. The tablets were formulated by direct compression technique using excipients like Sodiumcarboxymethylcellulose, carbopol934P and HydroxypropylmethylcelluloseK4M, PEG6000, magnesium stearate, talc and lactose. The compressed tablets were characterized for pre compression parameters such as angle of repose, bulk density, tapped density, Carr’s index, Hausner’s ratio and also post compression parameters like weight variation, drug content, thickness, hardness, swelling index, wash out time, mucoadhesive strength and in vitro drug release. All Formulated tablets showed satisfactory results for pre-compression and post-compression parameters. Among all formulations, F3 with combination of carbopol934P and sodium carboxymethyl cellulose showed greater in vitro drug release of 96.84 after 24 hrs, better mucoadhesive strength and good swelling. Hence formulation F3 was optimized and the stability studies were carried out according to ICH guideline which showed that the formulation F3 was stable after storage at 40±2°C and 75%±5% RH for three months.